Transformation to a market economy in Eastern Europe, the former Soviet Union and Asia - Marangos, John (2004)
Introduction -- Inconsistencies in the transition processes -- Lack of institutions and rise of corruption and crime in transition economies -- Alternative transition processes -- Conclusion.